Cold hard truth on men, women & money : 50 common money mistakes and how to fix them - O'Leary, Kevin, 1954- (Gallery Books, 2013)
The star of ABC's "Shark Tank" offers foolproof financial advice that will guide you through life's financial milestones so you can invest, spend, and save the smart way--no matter how old you are or how much you earn.